A Cross-Cultural Comparison of Negative Career Thoughts. (November 2016) - Lee, Donghyuck; Peterson, Gary W.; Sampson, James P.; Park, Meejin
This study explored similarities and differences of negative career thoughts in a sample of 1, 562 Americans and 3, 811 South Koreans by analyzing mean scores, item endorsement rates, and factor structures of the career thoughts inventory (CTI). A comparison of mean scores of the CTI scales showed that Koreans scored significantly higher on all scales than did Americans among high school, college, and adult participants. However, a comparison of ranks of item endorsement rates indicated that they were very similar. A confirmatory factor analysis indicated that the original three-factor solution of the normative data was a good fit for the United States across all age-groups but was not for the normative data of the respective age-groups from South Korea. Follow-up exploratory factor analyses identified possible alternative internal structures of the Korean CTI. Implications of the findings regarding plausible cultural influences on negative career thoughts as well as the use of the CTI in career counseling with members of the United States and Korean cultures are discussed.